2014
DOI: 10.1111/cei.12279
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in immune cell subsets and their cytokine secretion profile in childhood idiopathic thrombocytopenic purpura (ITP)

Abstract: SummaryImmune thrombocytopenic purpura (ITP) is acquired autoimmune disease in children characterized by the breakdown of immune tolerance. This work is designed to explore the contribution of different lymphocyte subsets in acute and chronic ITP children. Imbalance in the T helper type 1 (Th1)/Th2 cytokine secretion profile was investigated. )] cytokines were measured using enzyme-linked immunosorbent assay (ELISA). The percentage of Treg (P < 0·001) and natural killer (NK) (P < 0·001) cells were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
60
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 63 publications
14
60
4
Order By: Relevance
“…Rituximab, an anti-CD20 monoclonal antibody that depletes B cells, has been used to treat ITP for about a decade and has shown its efficacy in a subpopulation of ITP patients [25,26]. Our result, in agreement with previous studies [27][28][29], reported an increased frequency of B cells in ITP patients.…”
Section: Discussionsupporting
confidence: 92%
“…Rituximab, an anti-CD20 monoclonal antibody that depletes B cells, has been used to treat ITP for about a decade and has shown its efficacy in a subpopulation of ITP patients [25,26]. Our result, in agreement with previous studies [27][28][29], reported an increased frequency of B cells in ITP patients.…”
Section: Discussionsupporting
confidence: 92%
“…72 Several studies have shown lower frequencies and/or impaired function of Tregs in adults as well as in children with ITP. [73][74][75][76][77] Although the exact mode of action remains For personal use only. on May 7, 2018. by guest www.bloodjournal.org From unclear, IVIg treatment might restore the immunologic balance by inducing Tregs and so might influence the clinical course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…72 Several studies have shown lower frequencies and/or impaired function of Tregs in adults as well as in children with ITP. [73][74][75][76][77] Although the exact mode of action remains unclear, IVIg treatment might restore the immunologic balance by inducing Tregs and so might influence the clinical course of the disease. In children with lower platelet counts and higher bleeding tendency, both associated with a lower rate of chronic disease, treatment will be instituted more often than in children with higher platelet counts or a low bleeding tendency.…”
Section: Org Frommentioning
confidence: 99%
“…Monoclonal antibodies against FcγRIIIa have been shown to be effective in improving thrombocytopenia in ITP (22,23). Third, elevated Th2 cytokines (IL-4, IL-10) have been observed in patients with ITP (24). Fourth, decreased regulatory T (Treg) cells exhibiting impaired function have been observed in ITP patients (25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%